1996
DOI: 10.1016/0165-1889(95)00907-8
|View full text |Cite
|
Sign up to set email alerts
|

Asset and commodity prices with multi-attribute durable goods

Abstract: Montréal novembre 1995Ce document est publié dans l'intention de rendre accessibles les résultats préliminaires de la recherche effectuée au CIRANO, afin de susciter des échanges et des suggestions. Les Les organisations-partenaires / The Partner Organizations•Ministère de l'Industrie, du Commerce, de la Science et de la Technologie.•École des Hautes Études Commerciales.•École Polytechnique.•Université de Montréal.•Université Laval.•McGill University.•Université du Québec à Montréal.•Bell Québec.•La Caisse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…For excellent surveys on equity premium and risk-free rate puzzles see Cochrane and Hansen (1992) and Kocherlacota (1996). 2 See, for example, Mehra and Prescott (1988), Reitz (1988), Abel (1990), Constantinides (1990), Ferson and Constantinides (1991), He and Modest (1995), Constantinides and Duffie (1996), Detemple and Giannikos (1996), Heaton and Lucas (1997), Hindy and Zhu (1997), Campbell and Cochrane (1999), Zhou (1999), Constantinides et al (2002), Danthine et al (2004), Gordon and St-Amour (2004), DaSilva and Giannikos (2004), Storesletten et al (2007), Donaldson and Giannikos (2009) and Giannikos and Shi (2009). discount rate, and the intensity of non-addictive habit formation validated by previous studies. Giannikos and Shi (2009) present evidence that model specifications with both durability and habit persistence are able to match the high level of equity premium observed in the US data.…”
Section: Introductionmentioning
confidence: 99%
“…For excellent surveys on equity premium and risk-free rate puzzles see Cochrane and Hansen (1992) and Kocherlacota (1996). 2 See, for example, Mehra and Prescott (1988), Reitz (1988), Abel (1990), Constantinides (1990), Ferson and Constantinides (1991), He and Modest (1995), Constantinides and Duffie (1996), Detemple and Giannikos (1996), Heaton and Lucas (1997), Hindy and Zhu (1997), Campbell and Cochrane (1999), Zhou (1999), Constantinides et al (2002), Danthine et al (2004), Gordon and St-Amour (2004), DaSilva and Giannikos (2004), Storesletten et al (2007), Donaldson and Giannikos (2009) and Giannikos and Shi (2009). discount rate, and the intensity of non-addictive habit formation validated by previous studies. Giannikos and Shi (2009) present evidence that model specifications with both durability and habit persistence are able to match the high level of equity premium observed in the US data.…”
Section: Introductionmentioning
confidence: 99%
“…The general equilibrium of economies with adjustment costs has been studied by a few authors (e.g. Detemple and Giannikos (1996) and Mamaysky (2001)), but not with heterogeneous agents. 3 For the cross-sectional distribution not to collapse as t → ∞, a source of idiosyncratic risk in addition to aggregate risk is needed (see Caballero (1993) for a detailed discussion).…”
Section: Testing Implications Of the Frictionless Economymentioning
confidence: 99%
“…The theoretical effects of durability on portfolio choice have been studied by Grossman and Laroque (1990), Hindy and Huang (1993), Detemple and Giannikos (1996), Hindy et al (1997), Cuoco and Liu (2000) and by Damgaard et al (2003). In a constant investment opportunity set environment, it has been shown that an investor with preferences of the CRRA class defined over both a perishable and a durable good will find optimal to set constant portfolio weights over the time.…”
Section: Durability Of Consumption Goodsmentioning
confidence: 99%